Tenofovir plus entecavir combination therapy for chronic hepatitis B with nucleos(t)ide analogue failure - Tatar, Bengü; Köse, Şükran (The European Research Journal, 2020)
Objectives: Currently, both entecavir (ETV) and tenofovir (TDF) are recommended ﬁrst-line therapy for chronic hepatitis B treatment due to good tolerance, lower side-effect profile and high genetic barrier. However, mutations that may develop in the polymerase gene during treatment may result treatment failure. In this study, we aimed to evaluate the efficacy and virologic response of ETV plus TDF combination therapy in chronic hepatitis B patients with suboptimal response to nucleos(t)ide analogues (NAs) monotherapy. Methods: A total of 813 patients who were followed-up with the diagnosis of chronic hepatitis B and who were treated with TDF or ETV monotherapy were screened. Patients who had a partial or non response to monotherapy during at least 12 months and who was the presence of serum HBV-DNA levels ≥ 2000 IU/mL at the time of initiation of the ETV plus TDF combination therapy were included. Results: Ten (1.2%) patients (9 TDF, 1 ETV) were identiﬁed to have had partial response (50%) or breaktrough (40%) or virologic rebound (10%) to monotherapy. The median age was 36.8 years (range, 22-55 years), and 5/10 (50%) patients were male. Of 10 patients, nine of achieved undetectable HBV-DNA (< 15 IU/mL) levels (50% of in 6 months and 90% of in 18 months) with combination therapy. One patient showed no response. Conclusions: Our results suggest that combination therapy is superior to the antiviral change in treatment failure with NAs. In addition, it is important to conduct HBV drug resistance analyzes to prevent false drug change in treatment.